The Interrogative Lawsuit in Jordanian Law: An Analytical Study on Its Legitimacy and Conditions for Acceptance - Al-Ma’aitah, Dr. Ahmad Suleiman Khalaf (International Journal of Business, Law, and Education, 2025)
This study examines the interrogative lawsuit in Jordanian law through a descriptive-analytical approach, focusing on its legal nature and defining it as a preventive judicial action aimed at clarifying the plaintiff’s legal position without claiming a right or enforcing an obligation. The lawsuit relies on a potential interest to avoid future legal disputes. The research highlights the absence of explicit legislative provisions regulating this lawsuit in the Jordanian Civil Procedures Law, which hinders its acceptance and effectiveness. Judicial practices vary between acceptance, rejection, and caution regarding this lawsuit. The study calls for legislative reform to explicitly regulate the interrogative lawsuit with clear conditions for acceptance to ensure preventive justice and legal stability. It also recommends enhancing judicial and doctrinal efforts to activate the role of this lawsuit in protecting rights before disputes arise.